1999
DOI: 10.1135/cccc19991159
|View full text |Cite
|
Sign up to set email alerts
|

Metal Ion Chelates of Lipophilic Alkyl Diazinyl Ketoximes as Hydrolytic Catalysts

Abstract: A series of lipophilic dodecyl hetaryl ketoximes (hetaryl = pyridin-2-yl, pyridazin-3-yl, pyrimidin-2-yl, pyrimidin-4-yl, pyrazin-2-yl as well as their methyl hetaryl homologues was synthesized and hydrolytic activity of their chelates with Co 2+ , Ni 2+ , Cu 2+ and Zn 2+ in a micellar matrix of hexadecyltrimethylammonium bromide or in homogeneous aqueous solutions was investigated using 4-nitrophenyl acetate, 4-nitrophenyl hexanoate and 4-nitrophenyl diphenyl phosphate as model substrates. While Co 2+ and Cu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…It has been previously reported that the complex formation of pyridineoximate anions with metal ions leads to an inhibitory effect on the cleavage of phosphate triesters, in contrast to an acceleration effect with carboxylic acid esters . The reason for this difference is unclear because mechanistically the nucleophilic substitution in both types of esters is quite similar.…”
Section: Resultsmentioning
confidence: 96%
“…It has been previously reported that the complex formation of pyridineoximate anions with metal ions leads to an inhibitory effect on the cleavage of phosphate triesters, in contrast to an acceleration effect with carboxylic acid esters . The reason for this difference is unclear because mechanistically the nucleophilic substitution in both types of esters is quite similar.…”
Section: Resultsmentioning
confidence: 96%
“…Materials and General Methods: All initial chemicals were commercially purchased and used as received without further purification. The ligand mpkoH was prepared as colorless needle crystals according to the literature method . Elemental analyses for C, H, and N were carried out with a CE‐440 (Leeman‐Labs) analyzer.…”
Section: Methodsmentioning
confidence: 99%
“…The ligand mpkoH was prepared as colorless needle crystals according to the literature method. [11] Elemental analyses for C, H, and N were …”
Section: Materials and Instrumentsmentioning
confidence: 99%